2013
DOI: 10.1186/1472-6823-13-41
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive detection of microvascular changes in a paediatric and adolescent population with type 1 diabetes: a pilot cross-sectional study

Abstract: BackgroundThe detection of microvascular damage in type 1 diabetes is difficult and traditional investigations do not detect changes until they are well established. The purpose of this study was to investigate the combined ability of nailfold capillaroscopy, laser Doppler flowmetry, retinal vessel analysis and 24-hr ambulatory blood pressure monitoring to detect early microvascular changes in a paediatric and adolescent population with type 1 diabetes.MethodsPatients aged between 8 – 18 years with type I diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 32 publications
5
40
0
Order By: Relevance
“…This vascular heterogeneity may be related to significant autonomic neuropathy disturbances among population with this disease. Some other reports confirmed our results [2] [16].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This vascular heterogeneity may be related to significant autonomic neuropathy disturbances among population with this disease. Some other reports confirmed our results [2] [16].…”
Section: Discussionsupporting
confidence: 83%
“…microhaemorrhages in participants with diabetes (t = −2.33, P = 0.03). They demonstrated a positive association between recent HbA1c and the number of microhaemorrhages (r = 0.44, P = 0.03) [2]. We also found that isolated and irregular enlarged loops were seen more frequently in cases with scleroderma pattern.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations